An empirical study on the impacts of multi-facet benefits on continued usage intention: evidence from carsharing services in China. (11th June 2021) - He, Minghua; Liang, Xiaobei
Adopting the need fulfilment perspective as a guiding framework and extending the trust related literature into the distinctive context of SE, this study examines the impacts of the three types of perceived benefits on satisfaction and continued usage intention as well as the moderating effects of hedonic benefit and trust. The proposed hypotheses are tested by SmartPLS 3.0 using data collected from 239 users of Didi Chuxing platform, a leading carsharing platform in China. Specifically, we find that: utilitarian, social, and safety benefits have positive impacts on satisfaction; hedonic benefit positively moderates the relationship between social benefit and satisfaction; whereas hedonic benefit shows no significant moderating impact on the relationship between utilitarian benefit, safety benefit and satisfaction; trust is positively associated with continued usage intention, partially mediates the path from satisfaction to continued usage intention, and also negatively moderates the relationship between satisfaction and continued usage intention. These findings have important theoretical and practical implications.